RELATIONS OF BRAND IMAGE TOCUSTOMERS BUYING DECISIONON GRAND INNA MUARA HOTEL PADANG - Zengga, Zengga; Chair, Ira Meirina; Abrian, Youmil (Journal of Home Economics and Tourism, 2013)
This study aims to describe the relations between brand image to customers buying decision room in hotel grand inna muara padang. This study is a descriptive correlational study. The study population as many as 1694 consists of guest during stay on grand inna muara hotel padang. The descriptive analysis of the results showed that brand image categorized excellent (56%) and categorized quite good (33%). TheÂ  descriptive analysis of the result results showed that customers buying decision categorized excellent (38%) and categorized quite good (26%). results of correlation pearson product moment showed have significant relationÂ  between brand image and customers buying decision on grand inna muara hotel. Correlation coefficient 0,254 and significant level 0,014. Keywords: brand image, customers buying decision.